Constitutive modeling of hardening-relaxation response of asphalt concrete in cyclic compressive loading. (15th April 2017) - Karimi, Mohammad M.; Tabatabaee, Nader; Jahangiri, Behnam; Darabi, Masoud K.
Highlights: Relaxation of hardening occurs under cyclic loading in asphalt concrete. Hardening relaxation increases potential of viscoplastic strain accumulation. Hardening relaxation is a function of accumulated recovered viscoelastic strain. Viscoelastic-viscoplastic with hardening relaxation-viscodamage model is developed. The numerical implementation has been developed for FE modeling. Abstract: Cyclic loading on asphalt concrete materials with a longer relaxation time and lower remaining stress lead to higher viscoelastic strain recovery. Consequently, more aggregate reorientation occurs and the rate of viscoplastic strain increases in subsequent cycles. The present study proposes a hardening relaxation constitutive relationship ( f HR ) as a function of accumulated recovered viscoelastic strain ε rve based on experimental observation. This model captures the initiation and evolution of hardening-relaxation during the relaxation time and/or stress reduction under cyclic loading. The model was then coupled with viscoelastic, viscoplastic and viscodamage constitutive relationships. The numerical schemes were implemented in Abaqus finite element software using the user-defined material subroutine. The coupled constitutive relationship was calibrated against cyclic, creep-recovery and creep tests at different stress levels. The proposed hardening-relaxation constitutive relationship was then validated against independent laboratory experiments with different loading scenarios. It was shown that the hardening-relaxation constitutive relationship substantially improved strain prediction at intermediate temperatures.